1982
DOI: 10.1159/000280826
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker Process of Ureteral Peristalsis in Multicalyceal Kidneys

Abstract: The mechanical activity of isolated strips from different areas of the pyeloureteral system was investigated in 10 pigs: calyx, renal pelvis, pyeloureteral junction and ureter. Additionally, electrical activity was measured in some pyeloureteral preparations using the sucrose-gap technique. Regular spontaneous activity with an average frequency of 9.5/min was recorded in calyceal strips, decreasing to 5.4/min in renal pelvis, 5.7/min in pyeloureteral preparations and to 1.2/min in ureteral preparations. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 8 publications
(12 reference statements)
2
24
0
2
Order By: Relevance
“…It has been envisaged that these atypical SMC drive neighbouring 'typical' SMC in the renal pelvis either directly [16,33] or indirectly [33]. A 'coupled linear oscillator' model of multiple pacemaker regions, envisages that the most proximal pacemaker regions fire at the greatest frequency [19,51]. Increased diuresis or wall distension have been suggested to increase the coupling between neighbouring pacemaker regions and induce the summation of this asynchronous activity to trigger action potential discharge and renal pelvis contraction at a frequency driven by the most proximal pacemaker region present [2,3,19,51].…”
Section: Electrical Recordings From Smc Of the Uutmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been envisaged that these atypical SMC drive neighbouring 'typical' SMC in the renal pelvis either directly [16,33] or indirectly [33]. A 'coupled linear oscillator' model of multiple pacemaker regions, envisages that the most proximal pacemaker regions fire at the greatest frequency [19,51]. Increased diuresis or wall distension have been suggested to increase the coupling between neighbouring pacemaker regions and induce the summation of this asynchronous activity to trigger action potential discharge and renal pelvis contraction at a frequency driven by the most proximal pacemaker region present [2,3,19,51].…”
Section: Electrical Recordings From Smc Of the Uutmentioning
confidence: 99%
“…A 'coupled linear oscillator' model of multiple pacemaker regions, envisages that the most proximal pacemaker regions fire at the greatest frequency [19,51]. Increased diuresis or wall distension have been suggested to increase the coupling between neighbouring pacemaker regions and induce the summation of this asynchronous activity to trigger action potential discharge and renal pelvis contraction at a frequency driven by the most proximal pacemaker region present [2,3,19,51]. However, simultaneous extracellular recordings from numerous sites on the sheep renal pelvis have revealed that only one pacemaker region on the pelvi-calyceal border is active at any one time and that the pathway of conduction might meander throughout the renal pelvis.…”
Section: Electrical Recordings From Smc Of the Uutmentioning
confidence: 99%
“…TEA is a putative activator of gap junction complex formation [10,11] and in both ves sels examined -tail artery and mesenteric artery -TEA induced oscillatory contractions. The pacemaker-like ac tivity induced by TEA has been observed in nonvascular smooth muscle [10,20] and is associated with an increase in gap junction number as measured by electron micros copy [10]. This activity is probably not solely the result of potassium channel blockade, a better known activity of TEA, as the concentrations used to induce oscillatory con tractions are significantly above those used to block potas sium channels [21], Furthermore, the lag (minutes) be tween addition of TEA and appearance of contractile oscillations is not characteristic of potassium channel blockade [21], but is most likely necessary for recruitment of gap junction complex formation.…”
mentioning
confidence: 99%
“…The origin of ureteral peristalsis in intact ureters is thought to be from a main pacemaking area in the pelvicalyceal border which has the steepest depolarization (Dixon and Gosling, 1973;Hannappel et al, 1982;Hanke et al, 1992;Lammers et al, 1996). Klemm et al (1999) thoroughly investigated the cells underlying pacemaker activity in the guinea pig upper urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, he suggested that ICC-like cells, cells morphologically similar to the intestinal "interstitial cells of Cajal", in the renal pelvis and the pelvicalyceal junction play an integrative role by acting as a conduit for the electrical signals of the pacemaker cells to the smooth muscle cells of the renal pelvis and the ureter (Klemm et al, 1999). Indications of spontaneously active smooth muscle cells present in the porcine urinary tract distal to the renal pelvis or the ureteropelvic junction have been reported before (Hannappel et al, 1982). In isolated ureter rings, the spontaneous activity could originate from solitary pacemaker cells whose own spontaneous activity would be subordinate to the pelvicalyceal pacemaking system in the intact urinary system.…”
Section: Discussionmentioning
confidence: 99%